On secondary new particle formation in China - Kulmala, M.; Petaja, T.; Kerminen, V. M.; Kujansuu, J.; Ruuskanen, T.; Ding, A. J.; Nie, W.; Hu, M.; Wang, Z. B.; ZJ Wu; L. Wang; Worsnop, D. R. (Frontiers of Environmental Science & Engineering, 2016)
Formation of new atmospheric aerosol particles is a global phenomenon that has been observed to take place in even heavily-polluted environments. However, in all environments there appears to be a threshold value of the condensation sink (due to pre-existing aerosol particles) after which the formation rate of 3 nm particles is no longer detected. In China, new particle production has been observed at very high pollution levels (condensation sink about 0.1 s(-1)) in several megacities, including Beijing, Shanghai and Nanjing as well as in Pearl River Delta (PRD). Here we summarize the recent findings obtained from these studies and discuss the various implications these findings will have on future research and policy. (C) Higher Education Press and Springer-Verlag Berlin Heidelberg 2016
Keywords: aerosol particles; atmospheric aerosol nucleation; boreal forest; cloud condensation nuclei; concentration; condensation sink; distributions; ENGINEERING; Environmental Sciences & Ecology; formation rates; galactic cosmic-rays; health-benefits; Heavily-polluted environments; Megacities; New; nucleation mode particles; number size; particle production; pearl river-delta; sulfuric-acid